New insights into distinct eco-epidemiological scenarios of canine visceral leishmaniasis in São Paulo state, Brazil: from diagnosis to parasite-host interaction - Guerra, Juliana Mariotti (2019)
Visceral leishmaniasis (VL), caused by the protozoan parasite Leishmania (Leishmania) infantum and transmitted to humans and reservoir hosts by female sandflies, represents a serious public health problem due to its continuous expansion to new areas and urban centers. In São Paulo (SP) state, Brazil, VL has a distinct temporal-geographic pattern dispersion, first appeared in the northwestern (NWSP) region, spreading in a southeastern (SESP) direction over time. The epidemiology and ecology of the disease in a particular region are determined by characteristics of the parasite, vertebrate hosts and invertebrate vectors species. Domestic dogs are widely considered to be the main reservoir of the parasite, that leads to the canine visceral leishmaniasis (CVL), which usually precedes human cases. The objectives of this doctoral thesis were to improve the cytopathological methods for direct diagnosis of CVL and to analyze the pathological and molecular fundamentals of host-parasite interactions from different eco-epidemiological scenarios in SP state, Brazil. In a first instance, we performed cytopathological methods as smear cytology (SC), liquidbased cytology (LBC), cell block (CB) and immunocytochemistry (ICC) in popliteal lymph nodes samples of dogs naturally infected with L. infantum to improve the CVL diagnosis. We showed that SC was the most accurate morphological diagnostic method (45.0%). Besides, LBC reduced the number of unsatisfactory cases (low sampled cell number), allowed excellent cellular preservation and the application of ancillary techniques, such as CB and ICC. CB-ICC alone or associated with SC demonstrated significantly higher sensitivity (70.00% and 72.00%, respectively) when compared to the SC alone (34.00%). CB-ICC showed to be more effective in the detection of infected animals with mild clinical signs and a promising tool to improve diagnosis of CVL and may be applied in routine epidemiological screening. Subsequently, lymph nodes samples of dogs naturally infected with L. infantum from NWSP and SESP of SP state were subject to a series of histopathology and immunohistochemistry (IHC) analysis to describe microscope lesions, parasite load, and cytokine profile. We evidenced differences between the two eco-epidemiologic scenarios of CVL in SP state. In SESP region, a marked subcapsular inflammatory infiltration and histiocytosis were noted in the popliteal lymph node tissues, while significantly higher parasite burden (p = 0.0004) and IHC scores of IL-1ββ (p = 0.0275) and IL-4 (0.0327) were observed in animals from NWSP area. A final study proposed the characterization of the parasite genotype in dogs naturally infected with L. infantum from SESP and NWSP areas. The deletion genotype of L. infatum on LinJ.31.2380 locus was predominantly identified in the SESP, with a frequency of 44.44%, while the non-deletion genotype was observed in 35.19% of the samples (p = 0.01945) from the NWSP area. Eight (14.81%) and three (5.56%) samples from NWSP demonstrated a third, mixed profile for the deleted site, representing heterozygosity equivalent and non-equivalent, respectively. This study showed no statistical difference among the specific genotype, the clinical status and the parasite load in the popliteal lymph node samples of the dogs. Differences in genetic profile of L. infantum population and in the host immune response associated with higher parasite burden in dogs can also contribute to explain the distinct eco-epidemiological patterns of VL in specific geographic regions of SP state, which requires the development of early/accurate diagnosis, better control and surveillance strategies to improve both public and animal health.